Pengembangan Ekowisata Berbasis Bambu dan Teknologi Informasi untuk Mendukung Restorasi Lahan Perbukitan Melalui Partisipasi Masyarakat Lokal - Erpurini, Wala; Leonandri, Dino Gustaf; Alamsyah, Nur (Jurnal Pengabdian Tri Bhakti, 2025)
Eco-tourism development in hilly areas often encounters environmental degradation and limited community capacity in tourism management and digital promotion. This program aims to enhance bamboo-based eco-tourism by empowering local communities through information technology to support land rehabilitation. The methods included participatory approaches, bamboo planting for land restoration, construction of bamboo-based tourism facilities, and digital literacy training covering online marketing, tourism information systems, and QR-code-based educational media. The results indicate that bamboo cultivation strengthens soil stability, reduces erosion risk, and improves the visual appeal of the tourism area. Furthermore, improved digital skills enabled communities to expand destination promotion and increase tourist interest through digital platforms. These findings suggest that integrating ecological conservation with information technology can enhance the competitiveness of local eco-tourism, promote community economic independence, and support sustainable, community-based tourism management.